Digital inclusion through WOTR’s FarmPrecise mobile application - Dominic, Ditty Maria; Niranjan, A. Alagu; Mittal, Nimisha; Sulaiman, Rasheed V.; Malhotra, Aayushi; Singaraju, Niyati; Sharma, Sheetal (International Food Policy Research Institute, 2024)
The majority of smallholder farmers in developing countries lack access to location-specific science-based information. Although digital advisory tools can potentially help such farmers in accessing information, often blanket recommendations and obsolete content shared through these digital tools discourage farmers from using them. Farmers need relevant information and knowledge which they can adopt in their specific situations, which can thus help them enhance their productivity and income from farming. Keeping these in view the Watershed Organization Trust (WOTR) developed FarmPrecise Application in 2019 with the support of Qualcomm Wireless Reach programme. WOTR adopted a holistic approach to digital tool deployment, especially for reaching women who often face barriers in digital access and proficiency. This comprehensive approach involved capacity building of women by providing digital skill trainings, building social capital to reach more women, and instilling a sense of empowerment among them by enhancing their participation in decision making. In this Good Practice Note, we highlight how FarmPrecise, an innovative digital solution developed by WOTR, is ensuring digital inclusion of women farmers and empowering them to overcome the barriers of gender digital divide.